Manajemen Kepala Sekolah Dalam Pendidikan Inklusi Di SDN Lemah Putro 1 Sidoarjo - Muhammad Ikhsan; Suyadi (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
At SDN Lemah Putro 1 Sidoarjo Elementary School, there is a program called inclusive education that gives special needs kids access to the educational system. The purpose of this study is to identify the management program for inclusive education, how it is being implemented, and the challenges that have been experienced at SDN Lemah Putro 1 Sidoarjo. This research employed a qualitative descriptive approach. The study's participants included class teachers, special assistant teachers, and school principals. gathering study data through interviews, observations, and documentation. The study's findings led to the creation of a school principal program for inclusive education, which included training for teachers, acceptance of children with special needs, curriculum adaptation, and the requirement for infrastructure to support the learning process. Keywords: children with special needs, management, inclusive education References Bafadal, Ibrahim, Manajemen Peningkatan Mutu Sekolah Dasar, Jakarta: Bumi Aksara, 2012, hal. 39 Baharuddin, Kepemimpinan Kepala Sekolah Dalam Era Otonomi Pendidikan, Jurnal elHarakah, Vol.63.No.1, Januari-April 2006, hlm 20 Depdiknas, PLB, Pedoman Umum Penyelenggaraan Pendidikan Inklusif, Jakarta: Direktorat Pembinaan Sekolah Luar Biasa, 2007, hal. 4 Lexy J Moleong, Metodologi Penelitian Kualitatif. (Bandung: PT Remaja Rosdakarya, 2013), h. 128 Mohamad Takdir Ilahi, Pendidikan Inklusif (Yogyakarta: Ar-Ruzz Media, 2013). hlm 39 Permen Pendidikan Nasional RI Nomor 70 Tahun 2009 Pasal 1 Sistem penyelenggaraan pendidikan peserta didik yang memiliki kelainan dan memiliki potensi kecerdasan dan/atau bakat istimewa